2007
DOI: 10.1104/pp.107.098103
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-Linked Proteins Are Reduced during Germination ofMedicago truncatulaSeeds

Abstract: Germination of cereals is accompanied by extensive change in the redox state of seed proteins. Proteins present in oxidized form in dry seeds are converted to the reduced state following imbibition. Thioredoxin (Trx) appears to play a role in this transition in cereals. It is not known, however, whether Trx-linked redox changes are restricted to cereals or whether they take place more broadly in germinating seeds. To gain information on this point, we have investigated a model legume, Medicago truncatula. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 98 publications
(131 reference statements)
4
127
0
1
Order By: Relevance
“…Recent proteomic studies, such as thioredoxin-trapping chromatography or labeled gel electrophoresis, both in combination with protein identification by mass spectrometry, have identified >180 potential TRX target proteins in plants (Motohashi et al, 2001;Balmer et al, 2003Balmer et al, , 2004bBalmer et al, , 2006Wong et al, 2004;Marchand et al, 2006;Alkhalfioui et al, 2007). However, the vast majority of these have yet not been experimentally verified, and in vitro methods appear to suffer from an inherent lack of specificity as chloroplast targets have been identified with cytosolic TRX as bait and vice versa (Meyer et al, 2008).…”
Section: The Largest Trx Group In Arabidopsis Consists Of Eight H-typementioning
confidence: 99%
“…Recent proteomic studies, such as thioredoxin-trapping chromatography or labeled gel electrophoresis, both in combination with protein identification by mass spectrometry, have identified >180 potential TRX target proteins in plants (Motohashi et al, 2001;Balmer et al, 2003Balmer et al, , 2004bBalmer et al, , 2006Wong et al, 2004;Marchand et al, 2006;Alkhalfioui et al, 2007). However, the vast majority of these have yet not been experimentally verified, and in vitro methods appear to suffer from an inherent lack of specificity as chloroplast targets have been identified with cytosolic TRX as bait and vice versa (Meyer et al, 2008).…”
Section: The Largest Trx Group In Arabidopsis Consists Of Eight H-typementioning
confidence: 99%
“…13 The proteins sensitive to redox potential, termed potential thioredoxin targets (PTTs), have been intensively investigated. 13 Here, we screened possible PTTs from the differentially expressed proteins (DEPs) by use of a known PTT database 13,[28][29][30][31][32][33] (Supplemental Table S3). About two-thirds of the DEPs matched known PTTs.…”
Section: Identification Of Differentially Expressed Proteins Ms and mentioning
confidence: 99%
“…Comparative studies of the two procedures were reported in some studies 1,32,49 . In each case, the two procedures were found to be complementary.…”
Section: The Two Methods Are Complementarymentioning
confidence: 99%
“…It is therefore possible to confirm whether the putative targets of Trx identified by the in vitro reaction are reduced in vivo. In a study with the legume, Medicago truncatula, more than half the 43 potential Trx targets identified by the in vitro mBBr-labeling reaction were also labeled in vivo during germination 1 . In addition, Yano & Kuroda 55 reported that rice aleurone ESP2, identified as putative targets of Trx, were degraded both in vivo and in vitro by a cysteine protease also activated by Trx.…”
Section: How To Confirm Specific Targets?mentioning
confidence: 99%